Ukrainian flora checklist. 14: family Violaceae (Malpighiales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: Euro+Med Plant Base 2025, Hassler 2025, POWO 2025. Results: Violaceae in the flora of Ukraine is represented by one genus Viola, which includes 36 autochthonous species and two subspecies (without type), three ergasiophygophytes, and also a number of hybrid forms, some of which are described in the status of notospecies. The name of the species V. montana is rejected (nomen rejiciendum), so it is replaced by V. elatior. Synonyms of V. hymettia are V. cretacea (cited for the southern Donetsk Forest-Steppe), V. lavrenkoana (southern Forest-Steppe and Steppe) and V. nemausensis sensu Klokov, non Jord. (Odesa region, Crimea). The species name V. nemausensis Jord. is synonymous with the type species V. tricolor (V. tricolor subsp. tricolor). The species V. rupestris in Ukraine is represented by two subspecies: the typical V. rupestris subsp. rupestris and V. rupestris subsp. glaberrima. Synonyms of the type species/subspecies V. rupestris are V. arenaria and V. rupestris subsp. glabrescens. The name V. nemoralis is synonymous with V. ruppii. In the POWO database, V. ruppii is mistakenly considered as a subspecies – V. canina L. subsp. ruppii (All.) Schübl. & G. Martens, but this combination is illegal (nomen illegitimum). The synonyms of V. saxatilis are V. elisabethae (described from the Mountainous Crimea) and V. vespertina (described from the Caucasus), which do not differ from V. saxatilis in morphological characters. In the POWO database, the names V. elisabethae and V. vespertina are given as synonyms of the subspecies V. tricolor subsp. subalpina Gaudin, but this name is illegal (nomen illegitimum). The data on the growth of V. caspia in Crimea is erroneous and refers to V. sieheana. The synonyms of V. stagnina are V. commutata sensu Klokov, non Waisb. and V. persicifolia Hegetschw. (the latter name is illegal – nomen illegiticum). Synonyms of V. suavis are V. donetzkiensis, V. jagellonica, V. pontica and V. cyanea, which were listed as separate species for Ukraine. The species V. tricolor L. s. str. (V. tricolor subsp. tricolor) is common in northern forest areas and its citation for Crimea is erroneous. In Crimea, only V. saxatilis grows in the group of V. tricolor aggr. species, which differs in the colour of its flowers, with a predominance of yellow ones.
Keywords: biodiversity, annotated list, distribution, species, subspecies, genus, family, systematics, nomenclature, synonyms, herbarium specimens